Saffron: A Data Value Assessment Tool for Quantifying the Value of Data Assets - Attard, Judie; Debattista, Jeremy; Brennan, Rob (My University, 2019)
Data has become an indispensable commodity and it is the basis for many products and services. It has become increasingly important to understand the value of this data in order to be able to exploit it and reap the full bene fits. Yet, many businesses and entities are simply hoarding data without understanding its true potential. We here present Saffron; a Data Value Assessment Tool that enables the quanti fication of the value of data assets based on a number of different data value dimensions. Based on the Data Value Vocabulary (DaVe), Saffron enables the extensible representation of the calculated value of data assets, whilst also catering for the subjective and contextual nature of data value. The tool exploits semantic technologies in order to provide traceable explanations of the calculated data value. Saffron therefore provides the first step towards the efficient and effective exploitation of data assets.
Keywords: Data value; Data governance; Data value monitoring; Data value assessment; Linked Data; Explainability